Enzyme-Assisted Water Extraction Optimization, Antioxidant Capacity and Phenolic Profiling of Extracts from Garcinia Mangostana Linn - Tan, Poh-Lee; Soo, Kelvin Quai-Siang; Khor, Yih-Phing; Abas, Faridah; Tan, Chin-Ping (Journal of Food Technology Research, 2022)
The application of enzymes in extraction processes within the food industry has not been widely explored. In this paper, an enzyme-assisted water extraction method was employed and optimized to extract the antioxidative and phenolic compounds from the pericarp of Garcinia mangostana L. Fractional factorial design (FFD) was developed to screen out the significant factors from five extraction parameters, including enzyme concentration, liquid-solid ratio, reaction temperature, pH and reaction time. Next, a central composite design approach was used to optimize the significant parameters after the screening process. The optimal conditions according to statistical analysis were 1.46% w/w of enzyme (Celluclast® 1.5L & Pectinex® Ultra SP-L) concentration, 22.80 liquid-solid ratio, reaction temperature of 30 °C, pH 3 and 30 min of reaction time. Under the optimized conditions, antioxidant activities indicated by the 2,2-Diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) values and total phenolic content obtained were 86.51%, 86.77% and 21.222 mg gallic acid equivalent (GAE)/g, respectively.